Nexus Between CO2 Emissions, Energy Use and Economic Growth in Nepal (Quest Journal of Management and Social Sciences, 2021)
Background: Economic growth in different economies comes with a cost of environmental degradation. The environment-growth nexus has come to the spotlight since scientists as well as policy-makers point out the threat of climate change and global warming all around the world. Nepal faces problems of pollution day by day raising a question about sustainable growth in the country. Such sustainability can be achieved by exploiting the water resources of the country which can be further used to generate cleaner forms of energy.Objective: This paper examines the interconnection between environmental degradation and economic growth in Nepal under the Environmental Kuznets curve’s framework and causal framework. These frameworks also incorporate energy variables such as electricity production, electricity and oil consumption at a disaggregated level to understand the energy growth nexus in Nepal.Method: The Auto-Regressive Distributed Lag model followed by TY Non-Granger Causality tests and variance decompositions are incorporated in the study to examine the EKC hypothesis and the nexus between energy and growth is analyzed through a multivariate framework.Result: Our result does not show the presence of the EKC hypothesis in the case of Nepal. However, the causal framework indicated that a percentage increase in electricity generation would lead to a reduction in carbon dioxide by 0.7%. The variance decomposition results showed that the impact of CO2 on GDP would decrease with horizons getting longer. On the other hand, the impact of electricity generation on CO2 on was found to be 78% in the longer horizon. Conclusion: Nepal should harness its potential of generating hydroelectricity to reduce environmental pollution as well as increase economic growth. Substituting the cleaner form of energy such as hydroelectricity can help in reducing the consumption of fossils and fuels as well as help in mitigating the pollution level in Nepal. This will further allow Nepal to be self-reliant since it has huge potential for generating hydroelectricity.